James and Paul : the politics of identity at the turn of the ages - Shillington, V. George (Fortress Press, 2015)
Here V. George Shillington seeks to understand both James and Paul as Jews engaged in different but complementary missions and concludes that the tension between those missions indicates a conflict between different politics of identity.--Provided by publisher.